NEWS OF EVIDENCE-BASED MEDICINE: RESULTS OF THE IMPROVE-IT TRIAL AND THEIR IMPLICATIONS FOR CLINICAL PRACTICE - S. Yu. Martsevich (Столичная издательская компания, 2015)
Key findings of IMPROVE-IT trial and their possible significance for clinical practice are discussed.